Effect of rhamnolipid-Aloe vera gel edible coating on post-harvest control of rot and quality parameters of ‘Agege Sweet’ orange - Adetunji, Charles Oluwaseun; Afolabi, Israel Sunmola; Adetunji, Juliana Bunmi (Agriculture and Natural Resources, 2019)
A local cultivar of sweet orange namely ‘Agege sweet’ constitutes a larger percentage among many citrus varieties planted in Nigeria, but there is a major setback in terms of extending its post-harvest shelf life. This work was designed to assess the effectiveness of a rhamnolipid coating to preserve the quality attributes of Agege sweet orange fruit during 8 wk ambient storage compared with that of Aloe vera gel. Petri plates were supplied with different treatments (volume per volume, v/v) of Aloe vera gel (0%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%) or rhamnolipid (0%, 0.25%, 0.5%, 1.0%, 1.5 %, 2.0%) and oranges were inoculated with a spore suspension of P. digitatum NSP01 spores. The solutions of rhamnolipid (2%) and Aloe vera gel (2%) were evaluated for their biocontrol activity on P. digitatum NSP01. The fruits were stored for 8 wk at 25ºC. The lesion area, firmness, and chemical composition were assessed. The oranges coated with Aloe vera gel and rhamnolipid significantly (p < 0.05) prevented loss in firmness, total soluble solids and titratable acidity and reduced the decay caused by P. digitatum NSP01. Therefore, the newly formulated rhamnolipid-Aloe vera edible coating could serve as a permanent substitute for chemical fungicides used in the management of diseases and pests affecting agricultural productivity.